PENGARUH OPINI AUDIT, UKURAN PERUSAHAAN, PERGANTIAN MANAJEMEN, AUDIT FEE DAN AUDIT TENURE TERHADAP AUDITOR SWITCHING (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Hidayatika R Fredlina Dwitami Edla; Yusralaini Yusralaini; Hanif Afriana Rheny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine and analyze empirically on how the influence of audit opinion, company size, management change, audit fees and audit tenure on auditor switching. The population used in this study were banking companies listed on the Indonesia Stock Exchange in 2015-2019. The sample used was 27 banking companies selected using the purposive sampling method. The data analysis method used logistic regression analysis (Logistic Regression) with the help of the IBM Statistical Package for Social Science (SPSS) version 25 program. The results of this study indicate that: (1) audit opinion has an effect on auditor switching with a significance level of 0.009 <0.05. (2) firm size has an effect on auditor switching with a significance level of 0.044 < 0.05. (3) management change has an effect on auditor switching with a significance level of 0.003 < 0.05. (4) audit fee has an effect on auditor switching with a significance level of 0.042 < 0.05. (5) audit tenure has an effect on auditor switching with a significance level of 0.000 < 0.05.Keywords: Auditor Switching, Audit Opinion, Company Size, Management Change. Audit Fee and Tenure Audit.